Anthropometric Study of Nasal Index in Medical Students of Nepal - Sah, Sanjib Kumar; Shah, Rajesh Kumar; Yadav, Amlesh Kumar; Chaudhary, Raju Kumar; Parajuli, Surya Bahadur (Annapurna Journal of Health Sciences, 2025)
Introduction: Nasal anthropometry, focusing on the nasal index, highlights ethnicity and gender specific variations influenced by genetics, environment, and evolution. This study aims to analyze the nasal index of medical students to provide insights into the anthropometric variations across gender and ethnic groups. Understanding these variations can contribute to the growing body of knowledge on human morphology and may have implications for clinical and surgical practices involving nasal anatomy.Methods: A descriptive cross sectional study was conducted among 135 medical students from 15th August 2024 to 30th November 2024. Data were collected on baseline history. Anthropometric measurements of the nose were taken using a vernier caliper. Data was entered in Microsoft Excel sheet, nasal index was calculated and analyzed using SPSS version 23. Descriptive statistics were used to summarize findings.Results: Mesorrhine was the most common nasal type overall 71 (52.6%), observed in 37 (52.9%) males and 34 (47.9%) females. Ethnically, mesorrhine was predominant among Brahmin/Chhetri 17(51.5%), Dalits 4(66.7%), and Madhesi 38(54.3%) students. Leptorrhine was frequent in Janajati (6, 42.9%), while hyperleptorrhine and hyperplatyrrhine were least common across all groups.Conclusion: The study reveals that mesorrhine nasal morphology was the most common type among both males and females, with subtle differences in distribution. Ethnically, mesorrhine predominates among Brahmin/Chhetri, Dalits, and Madhesi students, while leptorrhine is more common in Janajati individuals. Rare types, such as hyper leptorrhine and hyper platyrrhine, show minimal representation across genders and ethnicities, reflecting distinct anthropometric patterns.